Definitions of post-coronary artery bypass grafting myocardial infarction: variations in incidence and prognostic significance. (10th June 2019) - Belley-Cote, Emilie P; Lamy, André; Devereaux, P J; Kavsak, Peter; Lamontagne, François; Cook, Deborah J; Kennedy, Kevin; Vincent, Jessica; Ou, Yongning; Tagarakis, George; Whitlock, Richard P
Abstract: OBJECTIVES: Using data from the CORONARY trial ( n  = 4752), we evaluated the incidence and prognostic significance of myocardial infarction (MI) applying different definitions based on peak postoperative creatine kinase-MB isoenzyme and cardiac troponin levels. We then aimed to identify the peak cardiac troponin during the first 3 postoperative days that was independently associated with a 2-fold increase in 30-day mortality. METHODS: To combine different assays, we analysed cardiac troponins in multiples of their respective upper limit of normal (ULN). We identified the lowest threshold with a hazard ratio (HR) >2 for 30-day mortality independent of EuroSCORE and on- versus off-pump surgery. RESULTS: Depending on the definition used based on creatine kinase-MB, the incidence of MI after coronary artery bypass grafting (CABG) ranged from 0.6% to 19% and the associated HRs for 30-day mortality ranged from 2.7 to 6.9. Using cardiac troponin (1528 patients), the incidence of MI ranged from 1.7% to 13% depending on the definition used with HRs for 30-day mortality ranging from 5.1 to 7.2. The first cardiac troponin threshold we evaluated, 180xULN, was associated with an adjusted HR for 30-day mortality of 7.6 [95% confidence interval (CI) 3.4–17.1] when compared to <130xULN. The next independent threshold was 130xULN with an adjusted HR for 30-day mortality of 7.8 (95% CI 2.3–26.1). The next cardiac troponin tested threshold (70xULN) did not meet criteria for significance. CONCLUSIONS: Our results illustrate that the incidence and prognosis of a post-CABG MI varies based on the definition used. Validated post-CABG MI diagnostic criteria formulated from their independent association with important clinical outcomes are needed.